2022
DOI: 10.1164/rccm.202110-2335oc
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of 6-Month Outcomes of Survivors of COVID-19 versus Non–COVID-19 Critical Illness

Abstract: Author Contributions: Drs Serpa Neto and Hodgson had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 33 publications
5
32
3
1
Order By: Relevance
“…This result suggests that COVID-19 initiates a greater acute burden of care than other illnesses with a similar level of initial respiratory compromise. This is perhaps in contrast to Hodgson's finding of comparable rates of new disability in both COVID+ and COVID− at 6 months post mechanical ventilation for acute respiratory failure [26].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…This result suggests that COVID-19 initiates a greater acute burden of care than other illnesses with a similar level of initial respiratory compromise. This is perhaps in contrast to Hodgson's finding of comparable rates of new disability in both COVID+ and COVID− at 6 months post mechanical ventilation for acute respiratory failure [26].…”
Section: Discussioncontrasting
confidence: 96%
“…Specifically, those presenting to an ED with SpO 2 < 90% on RA, requiring oxygen > 3 L/min to stabilise, were more likely to need mechanical ventilation and/or inpatient rehabilitation, whereas factors of age, comorbidity or BMI had less impact on care trajectory. The duration of mechanical ventilation correlated with a need for inpatient rehabilitation, in keeping with the known impact of ICU-AW, irrespective of the effects of COVID-19 [14,26]. This association complements the impact of mechanical ventilation duration on muscle weakness, the rate of mobility progression and new disabilities in COVID-19 reported elsewhere [25,35,36].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This result should be interpreted with caution because it could be explained by the overlap of ARDS sequelae ( 25 , 26 ), the so-called postintensive care syndrome (PICS) ( 27 ) and the post-COVID syndrome ( 28 ). Interestingly, a study performed by Hodgson and colleagues ( 29 , 30 ) showed that COVID-19 and non-COVID-19 PICS at 6 months after ICU admission are at least phenotypically similar, with similar post-ICU care. Be that as it may and consequently, these critical survivors have a high consumption rate of health resources ( 31 ) that must be managed in an adequate post-COVID care unit.…”
Section: Discussionmentioning
confidence: 99%
“…144 Reports of longer-term outcomes of survivors of ARDS with COVID-19 are emerging and provide evidence of persistent physical, mental, and cognitive deficits. 15,16,[145][146][147][148] Evidence of persistent interstitial lung disease in patients with ARDS related to COVID-19 who were mechanically ventilated has been reported, but there remains uncertainty as to how relevant this evidence is to a population of patients with non-COVID-19 ARDS. 10,149,150 Of note, some studies have shown better health-related quality of life, 16 and higher return to work rates in patients with COVID-19 ARDS compared with a non-COVID-19 ARDS population.…”
Section: Sequelae Of Ardsmentioning
confidence: 99%